Penyuluhan Perencanaan dan Tata Kelola Pembangunan Rintisan Kawasan Desa Wisata Terpadu Lontrong Anggur Kelurahan Debong Tengah Kecamatan Tegal Selatan - Agus Prasetyo Utomo; Novita Mariana; Saefurrohman Saefurrohman (Universitas Teuku Umar, 2023)
Indonesia has significant potential for driving transformation in social, cultural, and economic aspects with its numerous villages and urban communities. The number of tourist villages has grown from 1,302 in 2014 to 1,734 in 2018, indicating their evolution. However, villages still need to recognize the untapped potential and underutilized infrastructure that can be utilized for progress. The UNISBANK Semarang community engagement initiative seeks to empower villages, such as the Kelompok Wanita Tani (KWT) Lestari Barokah in Tegal Selatan, Kota Tegal. The project aims to boost local inspiration and aspirations while supporting the creation of Lontrong Anggur, a rural tourism initiative. The project divides into three main phases: enhancing skills and assistance, ongoing evaluation of Lontrong Anggur's advancement, and optimizing local resources. The project has facilitated the identification and optimization of local potential in KWT Lestari Barokah and similar villages. This has led to the development of ventures such as oyster mushroom cultivation, vegetable farming, and Arabian chicken breeding. Additionally, it has supported the establishment of Lontrong Anggur. This initiative aims to improve the self-sufficiency and overall growth of villages in economic, social, and cultural aspects.